Egress Safety for STUDIO Residential Buildings - Khaliunaa Darkhanbat; Inwook Heo; Kang Su Kim; Seung-Ho Choi (Buildings, 2024)
In recent years, the number of studio residential buildings has increased significantly in Korea, as well as in many other countries, due to changes in living patterns. In Korea especially, there have been many fire accidents in studio residential buildings, which have caused a huge number of casualties and property damages, because the buildings were not adequately equipped for firefighting. In this study, the egress safety of a typical studio residential building in Korea is analyzed. Fire simulations were performed with variables of the fire location and the capacity of the smoke exhaust system to estimate the available safe egress time (ASET); egress simulations were also performed with the variable of egress delay time, and the required safe egress time (RSET) was determined. Then, the egress safety was evaluated, and the criteria for egress safety evaluation were proposed based on the simulation results. A studio residential building with a floor plan different from the prototype was used to validate the proposed egress safety criteria. Finally, a simple evaluation model is presented to estimate the required safe egress time (RSET) without simulation and to examine the impact of bottlenecks.